A Glimpse Into the Secure Diversionary Treatment Program. - LOVELL, ALLIE (Corrections Today)
The article highlights that the Virginia Department of Corrections (VADOC) identified a critical need to develop innovative strategies in reducing the placement of inmates with Serious Mental Illness (SMI) in Restrictive Housing who display disruptive behaviors requiring additional security protocols and practices. It also discusses that Virginia Department of Corrections created an additional mental health code designation that would identify in mates with a Serious Mental Illness.